Effects of edible bird’s nest on ovary and uterus of cycling sprague dawley rats subjected to cadmium toxicity - Abdul, Quddus (2021)
Cadmium (Cd), an abundant heavy metal which is continually released into the environment by human economic activities, causes severe health damages. Humans and animals are mainly exposed to this toxic metal through occupation, diet, respiration, smoking, and water. Various studies on female rats have revealed that Cd accumulates in the female reproductive tract with a considerably quite long biological half-life and causes reproductive dysfunctions. The edible bird’s nest (EBN) is made from the salivary secretions of male swiftlet birds (Aerodramus fuciphagus and Aerodramus maximus). EBN is traditionally consumed for its medicinal and nutritional values. As of today, no prior studies have detailed out the effects of EBN on Cd-mediated reproductive toxicity in female animals. Therefore, this study was designed to investigate EBN’s ameliorating role against Cd toxicity induced reproductive dysfunction in cycling female rats. Thirty (30) female Sprague Dawley rats were assigned into five groups as follows: group 1, control (C) received distill water; treatment group 2 (T0) was administered with CdCl2 (5mg/kg BW); while group 3 (T1), group 4 (T2) and group 5 (T3) were administered with CdCl2 (5mg/kg BW) and graded concentrations of 60, 90 and 120 mg/kg BW of EBN via oral gavage respectively. After four weeks of the challenge, the experimental rats were euthanised under general anesthesia for blood and Uterine and Ovarian tissue sample collection. Histomorphometric analysis of the tissues were employed using H&E staining, while assessment of expressions of metallothionein (MT), vascular endothelial growth factor (VEGF), epidermal growth factor (EGF) and epidermal growth factor receptor (EGFR) were assessed by using Immunohistochemistry and measurement of plasma levels of estradiol (E2) and progesterone (P4) were done by using ELISA, Cd levels in uterine and ovarian tissues were assessed through ICP-MS. Oral administration of cadmium chloride (CdCl2) without EBN supplement (T0) resulted in significantly (p<0.05) higher accumulation of Cd (238.9 ± 23.7, 237.9 ± 37.3 ppb) in uterine and ovarian tissues respectively compared with the group C (3.3 ± 0.5, 4.2 ± 0.4) and other treatment groups (T1: 125.4 ± 16.1, 99.2 ± 5.9; T2: 89.3 ± 15.6, 84.8 ± 6.0; T3: 65.7 ± 12.0, 41.3 ± 3.6 ppb). The deposition of Cd in both tissues appeared to decrease with EBN supplement in a dose dependent manner. Meanwhile, increased immunohistochemical expressions of MT in uterine and ovarian tissues as assessed by number of positive stained cells was found in T0 compared to the C and other treatment groups (Uterus= C: 55 ± 2; T0: 109.3 ± 2.1; T1: 87 ± 2.5; T2: 78.3 ± 2.0; T3: 62.3 ± 0.8; Ovaries= C: 0.3 ± 0.3; T0: 3.0 ± 3.0; T1: 1.3 ± 0.3, T2: 0.6 ± 0.3, T3: 0.3 ± 0.3, staining intensity, p<0.05). On the other hand, a significant decrease (p<0.05) in the activity of superoxide dismutase (SOD, µ/mL) in T0 (0.0783± 0.0017) compared with the C (0.180 ± 0.001) and EBN supplemented groups (T1: 0.1 ± 0.0013; T2: 0.1 ± 0.0016; T3: 0.1 ± 0.0021) were found. There was a significantly (p<0.05) evident increase in thiobarbituric acid reactive substance (TBARS) levels in Cd only treated group as compared with negative control and EBN supplemented groups (C: 30.98 ± 2.7; T0: 35.8 ± 3.09; T1: 33.8± 2.18; T2: 25.85 ± 3.7; T3: 23.4 ± 3.7, nmol/mL). Moreover, the Cd only treated group revealed uterine histopathological changes which include cystic glands, loss of normal structure of luminal epithelium (LE) and glandular epithelium (LE) cells. While animals treated with Cd and EBN resulted in a significantly low level (p<0.05) of Cd in uterus and ovaries and lower uterine MT expression, lower degenerative changes of the LE and GE cells with normal histomorphology of glands as well as increased antioxidant SOD activity compared to Cd only treated group. Animals administered with only Cd resulted in decreased immunohistochemical expressions of VEGF (C: 86.33± 1.5; T0: 84.66± 3.17; T1: 108.3± 4.3; T2: 122.66± 4.9; T3: 132 ± 4.58, no of deterred cel +ve stained cells, p<0.05) , EGF (C: 80.66± 3.5; T0: 73 ± 2.64; T1: 93.33 ± 2.7; T2: 115.33 ± 2.33; T3: 121 ± 3, no of +ve stained cells, p<0.05) and EGFR (C: 96.33± 3.2; T0: 67.8 ± 0.98; T1: 108.33± 4.37; T2: 122.66 ± 4.91; T3: 141.3 ± 3.28, no of positive stained cells, p<0.05) in uterine tissues.. While animals treated with CdCl2 and EBN at three different dosages resulted in higher VEGF, EGF and EGFR expressions compared to Cd only treated group. The higher degree expressions for the growth factors (VEGF, EGF, EGFR) in the EBN supplemented groups compared to even the untreated control group reflects the strong ameliorating effect of EBN that surpasses the toxic effect of Cd exposure. The respective plasma concentrations of E2 and P4 (ng/L) in all treated groups (T0: 3.8± 0.1, 2.8± 0.1; T1: 4.5± 0.3, 4.5± 0.2; T2: 5.6± 0.1, 5.6± 0.2; T3: 7.0 ± 0.3, 6.1± 0.3) decreased significantly (p<0.05) in comparison with the control (C: 9.8± 0.3, 6.7± 0.3). Concentrations of E2 was significantly higher (p<0.05) in T3 as compared to other treated groups. Plasma P4 concentration decreased significantly in T0 as compared to control. The plasma P4 concentration in all EBN treated groups was significantly increased compared with the Cd-only group; with T3 showing a significantly higher (p<0.05) concentration. Meanwhile, CdCl2 found to have no significant impact on the estrous cycle length (4-5 days) across experimental groups; cells from vaginal smear showed normal morphology. Overall, the findings of this study revealed that oral exposure to Cd at a dose of 5 mg/kg BW results in significant alterations in the uterus and ovaries as evidenced by high Cd levels in these tissues and higher degree (p<0.05) of MT expression along with reduced antioxidant activity and histomorphological changes. Meanwhile, EBN proved to play a significant protective role against Cd-induced reproductive toxicity; the protection was higher at the dose rate of 120mg/kg. The low level of Cd deposition paralleled with reduced degree of MT expressions found in both the uterine and ovarian tissues of EBN supplemented groups that lead to an interesting conclusion of EBN’s potential role as a chelating agent for Cd, though its mechanism is something to be explored in future. In general, this study suggests that EBN has an ameliorating effect against Cd-induced reproductive toxicity. It protects and improves functions of the uterus and ovaries through its potent antioxidant activity, enhancing expressions of growth factors (EGF, EGFR, and VEGF), prevention of Cd deposition along with a rise in plasma levels of E2 and P4.